2009
DOI: 10.1182/blood.v114.22.4890.4890
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells in Patients with Multiple Myeloma and Monoclonal Gammopathy of Undetermined Significance.

Abstract: 4890 Background Myeloid-derived suppressor cells (MDSC) are a heterogeneous population of cells of myeloid origin, and include immature macrophages, granulocytes, dendritic cells (DC) and other myeloid cells. In mice, are phenotypically characterized as CD11b+Gr-1+. Humans MDSC have an immature phenotype, including lineage negative (Lin-), CD14-, HLA-DR-, CD15+, CD34+, CD11b+, CD33+, and CD13+ cells. MDSC impair T-cell functions through secretion immunosuppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Patients with advanced-stage HL (stages III and IV) had more MDSCs than those with early disease, (stage I and II) (Parrinello et al, 2009b). The same investigators also reported on the levels of MDSCs in 22 patients with multiple myeloma (MM) at diagnosis and in 20 patients with monoclonal gammopathy of undetermined significance (MGUS) using flow-cytometry (Parrinello et al, 2009a). They observed that patients with MGUS showed the same number of MDSCs (CD11b + , CD13 + , CD34 + , CD14 ) , CD45 + ) in the peripheral blood as healthy controls while patients with MM had a significant increase in MDSCs (Parrinello et al, 2009a).…”
Section: Mdscs In Haemato-oncological Malignanciesmentioning
confidence: 98%
See 2 more Smart Citations
“…Patients with advanced-stage HL (stages III and IV) had more MDSCs than those with early disease, (stage I and II) (Parrinello et al, 2009b). The same investigators also reported on the levels of MDSCs in 22 patients with multiple myeloma (MM) at diagnosis and in 20 patients with monoclonal gammopathy of undetermined significance (MGUS) using flow-cytometry (Parrinello et al, 2009a). They observed that patients with MGUS showed the same number of MDSCs (CD11b + , CD13 + , CD34 + , CD14 ) , CD45 + ) in the peripheral blood as healthy controls while patients with MM had a significant increase in MDSCs (Parrinello et al, 2009a).…”
Section: Mdscs In Haemato-oncological Malignanciesmentioning
confidence: 98%
“…The same investigators also reported on the levels of MDSCs in 22 patients with multiple myeloma (MM) at diagnosis and in 20 patients with monoclonal gammopathy of undetermined significance (MGUS) using flow-cytometry (Parrinello et al, 2009a). They observed that patients with MGUS showed the same number of MDSCs (CD11b + , CD13 + , CD34 + , CD14 ) , CD45 + ) in the peripheral blood as healthy controls while patients with MM had a significant increase in MDSCs (Parrinello et al, 2009a). Although these results are preliminary, representing only data analysed by flow cytometry, they may indicate that MDSCs could play a role in the progression of MGUS to overt MM via different immunosuppressive and proangiogenic effects.…”
Section: Mdscs In Haemato-oncological Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation